COMPARACIÓN CINÉTICA Y BIOQUÍMICA DE TRES CEPAS DE Clostridium tetani, PARA LA PRODUCCIÓN DE TOXINA TETÁNICA - Ivonne del Socorro Gutiérrez-Rojas; Rubén Dario Godoy-Sarmiento; José Manuel Granados; Raúl Alberto Poutou-Piñales (Universitas Scientiarum)
In this study was compared the biochemical and kinetic behavior of three strains of Clostridium tetani:Harvard (Ha), Massachusetts (Ms) and Caracas (Ca), strains commonly used for the production of thetetanic toxoid. Biochemical tests for anaerobic microorganisms identification were done and cultures in5L reactor were developed, under the following conditions: Latham means Mueller “With” and “Without”sodium glutamate; 1% (v/v) of inoculum, initial pH 7.1 ± 0.2 (variable), 35ºC and 100 r.p.m. The resultsshowed similar biochemical characteristics between the strains including the ATCC 9441 control. Thekinetic behavior of the Ms and Ha strains was similar for all the evaluated parameters, obtaining greaterproductivity in cultures supplemented with 2.5g/L of sodium glutamate (Ms: Without: 625Lf/L.h andWith: 658Lf/L.h; Ha: Without: 610Lf/L.h and With: 658Lf/L.h). The Ca strain, produced greater amount ofbiomass (Ca: 0.5420g/L; Ms: 0.2721g/L and Ha: 0.2009g/L), nevertheless, its toxin productivity wassmaller (Without: 174Lf/L.h and With: 417Lf/L.h). These results discard the use of the Ca strain for theproduction of the toxoid, under the assayed fermentation conditions.